The Effect of Cinnamomum verum and saxagliptin on some biochemical parameters of the liver in male rats induced diabetes by alloxan - K.S, Huda; F. B, Ali; R. S, Mohammed (Journal of Neonatal Surgery, 2024)
sugar levels or hyperglycemia. To study the antidiabetic activity of aqueous extract of Cinnamomum verum in alloxan induced diabetic albino rats. The aqueous extract of cinnamon 100mg/kg and 200mg/kg was studied alone and in combination with conventional oral antidiabetic drugs like saxagliptin 5mg/kg in alloxan-induced diabetic albino rats measuring the level of liver enzymes Alanine transaminase, Aspartate aminotransferase. The study included 56rats divided into seven groups (8for each group) with weights ranging from 200-250mg, the first group was as a control group, the second group was injected with alloxan 120 /kg/b.w. and nicotinamide 50 mg/kg/b.w. The third diabetic group received treatment with 5 mg/kg/ b.w. of saxagliptin drug. The fourth diabetic group received treatment with 100 mg/kg/b.w. of cinnamon. The fifth diabetic group received treatment with 200 mg/kg/b.w. of cinnamon. The sixth diabetic group received treatment with 100 mg/kg/b.w. of cinnamon and saxagliptin (5 mg/kg/ b.w.). The seventh diabetic group received treatment with 200 mg/kg/b.w. of cinnamon and saxagliptin (5 mg/kg/ b.w.). The animals were scarified and the heart’s blood was extracted. where the serum was isolated to study the biochemical parameters of liver enzymes. The study’s findings demonstrated an increase in the effectiveness of liver enzymes as a result of the injection of alloxan, but after treatment with cinnamon and saxagliptin, the level of these enzymes decreased in the treatment groups and also demonstrated that 30 days treatment with saxagliptin (5mg/kg) orally exhibited a significant (P≤0.05) decrease in AST, ALT when compared to diabetic rats but there are no significant differences when compared with cinnamon treatment groups (100 and 200mg/kg) when administration alone. Also, the study show that the aqueous extract of cinnamon produced a significant lower the liver enzymes (ALP, AST) and the combination of Cinnamon with saxagliptin when given for 30 days in alloxan induced diabetic albino rats caused more significant reduction in liver enzyme level than either drug is given alone. Combination of aqueous extract of Cinnamon (100 and 200mg/kg) with saxagliptin (5mg/kg) orally for 30 days significantly (P<0.05) enhanced the livers enzyme lowering when compared to cinnamon (100 and 200mg/kg) and saxagliptin (5mg/kg) when administration alone and to diabetic group but there are no significant differences when compared with control group. This indicates that cinnamon enhances the therapeutic efficacy of saxagliptin when given in combination...